Integrative Description of Cryptic Tigriopus Species From Korea Using MALDI-TOF MS and DNA Barcoding - Yeom, Jisu; Park, Nayeon; Jeong, Raehyuk; Lee, Wonchoel (Frontiers in Marine Science, 2021)
MALDI Time-of-Flight Mass Spectrometry (MALDI-TOF MS) provides a fast and reliable alternative method for species-level identification of pathogens and various metazoans. Compared to the commonly used mitochondrial cytochrome c oxidase subunit I (mtCOI) barcoding, advantages of MALDI-TOF MS are rapid species identifications and low costs. In this study, we used MALDI-TOF MS to determine whether spectra patterns of different species can be used for species identification. We obtained a total of 138 spectra from individual specimens of Tigriopus, which were subsequently used for various cluster analyses. Our findings revealed these spectra form three clear clusters with high AU value support. This study validates the viability of MALDI-TOF MS as a methodology for higher-resolution species identification, allowing detection of cryptic species of harpacticoida. In addition, we propose a new species, Tigriopus koreanus sp. nov. by utilizing integrative methods such as morphological comparison, mtCOI barcoding, and MALDI-TOF MS.